3D-ZIF scaffold derived carbon encapsulated iron nitride as a synergistic catalyst for ORR and zinc-air battery cathodes. (January 2021) - Radwan, Amr; Jin, Huihui; Liu, Bingshuai; Chen, Zibo; Wu, Qian; Zhao, Xin; He, Daping; Mu, Shichun
Abstract: To commercialize fuel cells and metal-air batteries, it is intensely desirable but challenging to design highly active, earth-abundant, low-cost and stable oxygen reduction reaction (ORR) catalysts to replace rare, precious and unstable Pt-based ones. Among them, Fe3 N is one of the promising candidates to replace precious and unstable Pt-based ORR catalysis. Herein, to obtain Fe3 N nanoparticles encapsulated in carbon frameworks with rich doped nitrogen, Fe2 O3 nanoparticles are firstly prepared hydrothermally and converted to Fe3 N, and then 3D zeolitic-imidazole frameworks (ZIF) is applied as a scaffold unit, followed by pyrolysis under ammonia gas. The product annealed at 900 °C (ZFN-900) displays a higher half-wave potential (25 mV) than a carbon-supported Pt catalyst in alkaline media. Remarkably, as air electrodes of the zinc-air battery, it exhibits a raised power density peak at 115.8 mW cm −2 with respect to carbon-supported Pt (81.6 mW cm −2 ) in addition to outstanding durability. Such superior catalytic properties are broadly accredited to the chemical structure synergistic effect, extraordinary surface area, rich active sites, conductive carbon frameworks with highly nitrogen doping. Without a doubt, this method sets out a novel pathway for advantageous and extremely active catalysts with an adapted design for electrochemical energy systems. Graphical abstract: Image 1